Long-term response to ipilimumab after nivolumab failure in a case of anorectal melanoma with an intermediate tumor mutation burden and negative for PD-L1 expression - Sakai, Hitomi (Mol Clin Oncol, 2020)
Anorectal melanoma is a rare disease with a poor prognosis and its response to immunotherapy remains poorly studied. The current study reports a case of recurrent anorectal melanoma in a 60-year-old woman that has exhibited a durable response to ipilimumab for >2 years. Given that the combination of nivolumab and ipilimumab was not approved for use in unresectable or metastatic melanoma at the time of presentation, the patient was initially treated with nivolumab monotherapy and switched to ipilimumab after nivolumab failure. The tumor was microsatellite stable, had an intermediate tumor mutation burden and was negative for programmed cell death-ligand-1 expression. However, the neutrophil-to-lymphocyte ratio in peripheral blood remained at <5 throughout the disease course. Although mucosal melanoma is not caused by ultraviolet radiation and has a lower mutation burden than cutaneous melanoma, the present case responded well to immunotherapy. Further evaluation of potential biomarkers for such patients is required.